2016
DOI: 10.1088/2053-1583/3/3/034003
|View full text |Cite
|
Sign up to set email alerts
|

Weak localization and electron–electron interactions in few layer black phosphorus devices

Abstract: Few layer phosphorene(FLP) devices are extensively studied due to its unique electronic properties and potential applications on nano-electronics . Here we present magnetotransport studies which reveal electron-electron interactions as the dominant scattering mechanism in hexagonal boron nitride-encapsulated FLP devices. From weak localization measurements, we estimate the electron dephasing length to be 30 to 100 nm at low temperatures, which exhibits a strong dependence on carrier density n and a power-law d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
6
16
0
Order By: Relevance
“…[39]. Consistent with this conclusion, a weaker power-law dependence L ϕ ∝ T −0.4 was indeed very recently observed in another paper on few-layer bP, but nonetheless interpreted as evidence for electron-electron interactions in two dimensions as the dominant scattering mechanism [41].…”
Section: Discussionsupporting
confidence: 81%
“…[39]. Consistent with this conclusion, a weaker power-law dependence L ϕ ∝ T −0.4 was indeed very recently observed in another paper on few-layer bP, but nonetheless interpreted as evidence for electron-electron interactions in two dimensions as the dominant scattering mechanism [41].…”
Section: Discussionsupporting
confidence: 81%
“…The high mobility and small bandgap of BP indicate that the avalanche carrier multiplication is possible and BP is a promising active material for an APD. In addition, we note that the shorter carrier‐carrier scattering time compared to the carrier‐phonon scattering time in BP also results in the occurrence of avalanche carrier multiplication at a low applied voltage …”
Section: Comparison Of the Performance Of This Work (Nonavalanche Bp mentioning
confidence: 91%
“…This was explained by a quasi‐one‐dimensional behavior of bP due its pronounced crystalline anisotropy . The relevance of crystalline anisotropy was also highlighted in a recent in‐plane magneto‐transport study which showed an unexpected, non‐classical longitudinal magneto‐resistance .…”
Section: 2d Bp Stability Optimization and Device Propertiesmentioning
confidence: 81%
“…Weak localization was studied in few‐layer bP FETs, see Figure a. Weak localization is a quantum‐mechanical effect related to phase‐coherent scattering at low temperature and results in a resistance increase due to enhanced backscattering, as shown in Figure b.…”
Section: 2d Bp Stability Optimization and Device Propertiesmentioning
confidence: 99%